Socio-environmental and academic induced stressors as determinants of mental health among academic staff of Osun state college of education, Ila-orangun (2007)
The study attempts to identify the socio-academic induced stressors determining mental health of Academic Staff of Osun State College of Education, Ila-orangun. A total of one hundred (100) respondents were drawn from among the academic staff of the college, which represent about 50% of the population of academic staff The study revealed that the distance of some academic staff residences, publication, lack of basic amenities, internet facilities, inadequate teaching and learning facilities, student population explosion and elongated social calendar among others are the major Socio-Academic Stressors affecting the mental health of academic staff within the college